Putting Cities in the Framework of Sustainable Development; Evolution, Evaluation and Features of SDG 11 - METAXAS, Ioannis; METAXAS, Theodore (Journal of Environmental Management and Tourism; Vol 14 No 4 (2023): JEMT, Volume XIV, Issue 4(68), Summer 2023, 2023)
The purpose of this paper is to analyze in first basis, how the International Community, reached the adoption of the SDG’s goals, and to discuss the assets and the problems, the omissions of these goals. Then, this text will give emphasis to the inclusiveness, resilience, safety and sustainability of the cities, and will indicate the extent that those goals were well – promoted and protected under the Millennium Sustainable Development Goals (MDGs) and the Sustainable Development Goals. Moreover, this assignment, will trace the upgrade and integration of these goals into an entrenched and united goal (Goal 11 of Sustainable Development) and the current developments and problems that seem to emerge, mostly regarding the sustainability of the cities. Furthermore, this paper will try to prove the strong linkage between SDG 3 (Good Health – Well Being) and SDG 11.